Living in the big pond : adding the neighborhood as a frame of reference for academic self-concept formation - Becker, Dominik [Verfasser]; Fleischmann, Moritz [Verfasser]; Trautwein, Ulrich [Verfasser]; Nagengast, Benjamin [Verfasser]; Weßling, Katarina [Verfasser] (My University, 2024)
„Research on the big-fish-little-pond effect demonstrates that class-average achievement negatively affects students’ academic self-concept via social comparison processes. The neighborhood-effects literature reports positive effects of advantageous socioeconomic neighborhood conditions on students’ academic development via collective socialization mechanisms. To investigate how socioeconomic neighborhood conditions affect academic self-concept, we separately and simultaneously analyzed classroom- and neighborhood-level composition effects on students’ academic self-concept, using two samples drawn from two grade levels (= 3,906, = 3,277). Analyses of the neighborhood level only indicate that socioeconomic neighborhood conditions negatively predict general, math, and German self-concept in Grade 5. In Grade 9, this holds only for math self-concept. In simultaneous analyses including classrooms and neighborhoods, socioeconomically advantageous neighborhood conditions negatively predicted general and math self-concept in Grade 5.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.1 Allgemeinbildende Schule; 370; 300; Schüler; Selbstbild; Schulklasse; Leistungsfähigkeit; Leistungsvergleich; Unterrichtsfach; Sozioökonomische Faktoren